Chikungunya: an emerging and spreading arthropod-borne viral disease. - Francesca Cavrini; Paolo Gaibani; Anna Maria Pierro; Giada Rossini; Maria Paola Landini; Vittorio Sambri (Journal of Infection in Developing Countries)
The infection caused by the virus Chikungunya is known since the last 50 years, but since the disease was mainly diffuse in geographical areas located in developing countries, a few research work have been made available until the appearance of an important epidemiological outbreak in 2005 in the island of La Reunion, that is part of metropolitan France even if located in the Southern Eastern part of the Indian Ocean. In 2007, a smaller outbreak of Chikungunya developed in the Northern Eastern part of Italy, where the local transmission has been made possible by the enormous population of Aedes albopictus and the presence of a viremic patient coming from the Indian Ocean area. Nowadays, Chikungunya is spreading in Southeast Asia countries, including Indonesia, Malaysia, Thailand and Singapore. This paper reviews different aspects of the disease caused by Chikungunya virus, including: history, epidemiology, biological and pathogenetic aspects, clinical pictures, diagnosis and treatment.